Opportunistic Infections in Individuals Living with HIV/AIDS: What is the Situation Found in a Specialized Care Service Located in Northeastern Brazil? - Reis, Ana Beatriz de Oliveira; Gomes, Sávio Marcelino; Carmo, Egberto Santos (Revista Prevenção de Infecção e Saúde, 2024)
Introduction: Opportunistic infections are not uncommon in individuals living with the Human Immunodeficiency Virus (HIV), being one of the main causes of morbidity and mortality associated with Acquired Immunodeficiency Syndrome (AIDS). Aim: to conduct a survey on the prevalence of opportunistic infections in individuals living with HIV/AIDS assisted by a Specialized Care Service (SCS). Design: For this purpose, an epidemiological, analytical, and retrospective study was conducted, in which data collection was performed from patient records. The association of variables such as sex, age, education, income, treatment, viral load, CD4+ T lymphocytes, and opportunistic infection was verified through Fisher’s exact test to identify possible factors associated with infections. Results: From 2014 to 2020, 214 cases were reported, of which 65 had some opportunistic infection, the most frequent being: oral candidiasis (58.46%); cytomegalovirus (16.92%); pulmonary tuberculosis (12.31%); and herpes zoster (10.77%). A higher frequency was observed in males (73.85%); age between 20 and 59 years (44.61%); income below one minimum wage (50%); and incomplete elementary education (37.04%). There was no statistical significance (p<0.05) among the associated variables in the study. Implications: It can be concluded that oral candidiasis remains one of the main coinfections in individuals living with HIV/AIDS. Additionally, these results may contribute to the development of prevention strategies, reducing the number of cases of opportunistic infections, and improving the survival of individuals living with HIV/AIDS.